Axonal Alignment and Enhanced Neuronal Differentiation of Neural Stem Cells on Graphene‐Nanoparticle Hybrid Structures. (4th July 2013) - Solanki, Aniruddh; Chueng, Sy‐Tsong Dean; Yin, Perry T.; Kappera, Rajesh; Chhowalla, Manish; Lee, Ki‐Bum
<x xml:space="preserve">Abstract</x> Human neural stem cells (hNSCs) cultured on graphene‐nanoparticle hybrid structures show a unique behavior wherein the axons from the differentiating hNSCs show enhanced growth and alignment. We show that the axonal alignment is primarily due to the presence of graphene and the underlying nanoparticle monolayer causes enhanced neuronal differentiation of the hNSCs, thus having great implications of these hybrid‐nanostructures for neuro‐regenerative medicine. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>